Nalar Ideologis Penggunaan Hadis dalam Tafsîr al-Jalâlayn - Miski, Miski (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2017)
This study starts from the fact that the Qur’anic interpretation based on ?adîth could not be separated from the ideology of the exegetes. With the primary sources of Tafsîr al-Jalâlayn, by Jalâl al-Dîn al-Mah}allî and Jalâl al-Dîn al-Suyût}î, and by focusing on two main themes: theft and adultery, this study finds that the strategy they undertaken includes several processes, first: selection, that is by choosing the ?adîth of the Prophet around the law of hand cut in the case of theft, and the law of exile and stoning in the case of adultery, as a reference of interpretation, while there are many other options such as found in the Qur’an, the opinion of the Prophet Companions and tabi’in. Second, reproduction, that is, by actually choosing the sunna as a reference of interpretation. Third, conclusion, that is by providing generalization of the issue. Thus, it seems to argue that it is the only existing sunna and it is the only one that should be understood. Yet, there are many other sunna in its complexities, and even they are contradicting each other. Fourth, the local transformation, which displays the sunna in such a way.